Cephalopod distribution in Iskenderun Bay (Eastern Mediterranean-Turkey) - (:unkn) unknown (My University, 2008)
0

This paper is the first comprehensive work on the biology and distribution of cephalopods in the Iskenderun Bay area of Mediterranean Sea. Information on the distribution of Cephalopod fauna was collected through 45 deep-trawl surveys carried out on the commercial trawl fishery waters (between 20 and 200 m) between March 2004 and May 2005. During the study, a total of 1101 individuals belonging to eight species; two cuttlefishes, two squids and four octopods, were recorded. Mean value of dorsal mantle lengths and body weights of the captured species were; 10.74 ± 0.10 cm and 126.42 ±3.24 g for Sepia officinalis, 4.2 cm and 4.68 g for Sepia elegans, 15.3±0.42 cm and 87.68 ±6.35 g for Loligo vulgaris, 10.93 ±0.28 cm and 48.17 ±4.52 g for Illex coindetii, 8.08 ±0.13 cm and 99.17 ±4.01 g for Eledone moschata, 13.5 cm and 281.46 g for Eledone cirrhosa, 10.25±0.45 cm and 370.33 ±53.89 g for Octopus vulgaris, 12.71±0.64 cm and 405.59 ±51.69 g for Octopus macropus. In addition the present study also provides information on dorsal mantle length – body weight relationship and biology of the species found in this particular area.
Keywords: Balıkçılık